STRATEGI PENGEMBANGAN INDUSTRI KREATIF DENGAN TEMA BUDAYA PADA PRODAK KAOS SEBAGAI UPAYA MEMPERKENALKAN BUDAYA FLORES TIMUR - Said, Ardi; Maruto, Anom; Andayani, Sri (Jurnal Dinamika Administrasi Bisnis, 2019)
This research is aimed at 1). finding out the internal factors (strengths and weaknesses) of a corporation as the consideration for business decision making. 2). To find out the external factors (opportunities and threats) of a corporation as the consideration for a forward-looking marketing strategy of a company. 3). To determine the marketing strategy policy in accordance with SWOT analysis.Ex-post facto is utilized in this research design. This research is also used to delineate the real phenomenon in the field of the study. The research was conducted in one of the screen-printing business namely Tema Budaya Flores Timur in Surabaya. The subject of the research is the owner and the employee of the screen-printing business of Tema Budaya Flores Timur. The instrument of the research was conducted with the design of the activity at the screen-printing business of Tema Budaya Flores Timur.The result of the research revealed that the internal circumstances of the screen-printing business of Tema Budaya Flores Timur in Surabaya has its value at 22.8 which means that there is a good company value based on the Likert scale. However, the external condition of the screen-printing business has its value at 3.45 which means that it has the high opportunity according to Likert scale. The implementation of the working system at screen-printing business of Tema Budaya Flores Timur in Surabaya has the weight value item at 0.151 that means the company has the lowest threat rank than other threats. The screen-printing business is still in the growth phases. This could be seen from the internal and external SWOT matrix which reveals that the condition of the company at stage 1. Thus, strengths and opportunities (SO) strategy can be applied in Tema Budaya Flores Timur screen-printing business.Key words: SWOT analysis, marketing strategy.